Bioacoustic Spectral Profiling of the Endangered Salmon-Crested Cockatoo (Cacatua moluccensis) Using Fast Fourier Transform for Conservation Monitoring - Richard Rudolf Lokollo; Fredrik Manuhutu; Rony Marsyal Kunda (Jurnal Penelitian Pendidikan IPA, 2026)
The endangered Salmon-crested Cockatoo (C. moluccensis) is an endangered species endemic to Maluku and faces serious pressures due to habitat loss and illegal trade. As a species that relies heavily on vocal communication, bioacoustic analysis offers an effective, non-invasive approach to support monitoring and conservation. This study aims to analyze and characterize the spectral profile of Salmon-crested Cockatoo (C. moluccensis) vocalizations using the FFT algorithm. Voice recordings were conducted on individuals in their natural and captive habitats using a Zoom H5 Handy recorder. Audio data were processed through noise filtering, normalization, and segmentation stages before being analyzed using computational programming-based FFT to obtain the main spectral parameters. The results show that Salmon-crested Cockatoo (C. moluccensis) vocalizations have a consistent spectral structure with the main parameters being dominant frequency, bandwidth, spectral centroid, and amplitude. Spectral analysis shows variations in frequency characteristics influenced by environmental and individual conditions. The dominant frequency of Salmon-crested Cockatoo (C. moluccensis) behavior in its natural habitat was 1981 Hz, while in captivity it was 2497.9 Hz, both of which are within the main frequency range of ± 1500 – 4000 Hz. These different conditions show that frequency alone is not enough to explain behavior, but must be combined with context (call patterns, social interactions, and other behavioral expressions). The FFT method proved effective in identifying and characterizing vocalization patterns quantitatively. These findings indicate that FFT-based bioacoustic analysis has the potential to be developed as a non-invasive monitoring tool to support the conservation and population management of endangered endemic bird species.